"Change Won't Happen Without You" : Volunteer Recruitment and Organizational Website Rhetoric - Fredman, Amy (My University, 2012)
The purpose of this study is to look at the degree to which volunteer recruitment strategies found in extant literature appears on nonprofit organizations' websites and to explore how knowledge of volunteer recruitment strategies can be used to improve recruitment efforts.
Color poster with text and photographs.
Keywords: Volunteers--Recruitment; Web sites--Evaluation; Posters